Students' Perception Toward Artificial Intelligence - Taroreh, Shally Mercy; Liando, Nihta V. F; Rorimpandey, Rinny S (Program Studi Pendidikan Bahasa Inggris, 2024)
Abstract : The purpose of this study is to explore students’ perception toward AI. The research method used in this study was qualitative research with a descriptive approach. Qualitative research is descriptive and involves analysis. Processes and meanings (subjective perspectives) are emphasized in qualitative research. The theoretical framework is utilized as a guide to ensure that the research focus aligns with the facts in the field. a Likert scale with four options ranging from Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD). The data collection technique is closely related to the instruments that will be determined. Data collection is, of course, also related to the issues and research objectives, the Result show that the data analysis reveals a nuanced landscape of attitudes and concerns. While many students express enthusiasm about the potential benefits of AI-driven teaching methods, such as personalized learning experiences and improved access to educational resources, there is also a significant level of apprehension regarding the implications for traditional teaching methods and human interaction. The findings suggest that students value the role of human teachers as mentors, motivators, and facilitators of meaningful learning experiences, raising questions about the potential for AI to replace or diminish the quality of teacher-student.